Towards persuasive sociometric technologies for inclusive educational settings - Lyra, Olga; Karapanos, Evangelos; Gouveia, Rúben; Barreto, Mary L.; Nisi, Valentina; Nunes, Nuno J.; Zimmerman, John; Forlizzi, Jodi (My University, 2013)
With an increasing interest in the social inclusion of children in schools, HCI researchers have proposed technologies that support children at risk of social exclusion in their interactions with peers. However, much of this work has focused on the child at risk of social exclusion, disregarding the fact that social exclusion is a group-phenomenon that often originates in children's negative stereotyping. In this paper we argue for persuasive sociometric technologies, ones that sense children's social interactions in real-time, and provide persuasive, just-in-time recommendations to children with the goal of challenging their perceptions of diversity and motivating pro-social behaviors. We report on two studies that aimed at inquiring into children's practices of social exclusion in school communities as well as whether and how persuasive technologies can stimulate pro-social behaviors and a sense of empathy among them.
Keywords: Persuasive sociometric technologies; Social inclusion